2015
DOI: 10.1038/srep11831
|View full text |Cite
|
Sign up to set email alerts
|

Systematic characterization of the peroxidase gene family provides new insights into fungal pathogenicity in Magnaporthe oryzae

Abstract: Fungal pathogens have evolved antioxidant defense against reactive oxygen species produced as a part of host innate immunity. Recent studies proposed peroxidases as components of antioxidant defense system. However, the role of fungal peroxidases during interaction with host plants has not been explored at the genomic level. Here, we systematically identified peroxidase genes and analyzed their impact on fungal pathogenesis in a model plant pathogenic fungus, Magnaporthe oryzae. Phylogeny reconstruction placed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 71 publications
2
63
0
Order By: Relevance
“…A comparative analysis revealed that the retained gene in O . sinensis belongs to the Prx1 type, which was reported to be functionally conserved 27 and expressed only when the cells are exposed to high levels of H 2 O 2 generated exogenously 26 .
Figure 3Analysis of peroxidase genes and positive selection. ( A ) Comparisons of the percent and number (parentheses) of peroxidase genes among the five entomopathogenic fungi and yeast ( S .
…”
Section: Resultsmentioning
confidence: 99%
“…A comparative analysis revealed that the retained gene in O . sinensis belongs to the Prx1 type, which was reported to be functionally conserved 27 and expressed only when the cells are exposed to high levels of H 2 O 2 generated exogenously 26 .
Figure 3Analysis of peroxidase genes and positive selection. ( A ) Comparisons of the percent and number (parentheses) of peroxidase genes among the five entomopathogenic fungi and yeast ( S .
…”
Section: Resultsmentioning
confidence: 99%
“…However, DAB is a slow-acting stain (8-12 h) (Thordal-Christensen et al, 1997). Another method used for H 2 O 2 detection during plant-pathogen interactions is the fluorescent dye 2,7-dichlorodihydrofluorescein diacetate (H 2 DCDA) (Huang et al, 2011;Mir et al, 2015). H 2 DCDA is membrane permeable and fluoresces when oxidized but can leak over time or be easily saturated, thus skewing results (Tarpey, 2004).…”
Section: Traditional Toolsmentioning
confidence: 99%
“…Few studies have demonstrated that bioactive nutrients regulate adipocyte metabolism and differentiation. Fisetin, a flavonoid found in many fruits and vegetables, inhibits PPARγ acetylation in vitro (in 3T3-L1 cells) via Sirt1, while inhibition of Sirt1 activity induces PPARγ acetylation and thus contributes to increased lipid accumulation and adipocyte differentiation (Mir et al, 2015). Another phenolic compound (including chlorogenic acid, phloridzin, quercetin, catechin, epicatechin, procyanidin, and rutin), found at high concentrations in fruits such as apples, regulates adipogenesis by differentially regulating DNA methylation.…”
Section: Preventive Strategies: Drugs Targeting Epigenetic Modificmentioning
confidence: 99%